The Impact of Childhood Trauma in Jennifer Niven's Novel Holding Up the Universe (2016) - Hummairah, Citra; Hafizh, Muhd Al (English Language and Literature, 2023)
This study is an analysis of Jennifer Niven’s novel, Holding Up the Universe (2016) with the theme of childhood trauma. Childhood trauma is a prevalent issue in society, affecting both children and adults. This research aims to find out the causes of the character’s childhood trauma in the novel. The result shows that there are two causes of the character’s childhood trauma, namely the death of the character’s mother and bullying.